Nietzsche in Hollywood : Images of the Übermensch in Early American Cinema. - Rukgaber, Matthew (SUNY Series, Horizons of Cinema Ser., 2022)
Argues that Nietzsche's idea of the Übermensch was a central concern of filmmakers in the 1920s and 1930s.